Real Time Monitoring of Posture to Improve Ergonomics - Gopinath, Manju; Kirubha, Angeline (British Journal of Healthcare and Medical Research, 2015)
Back pain is one of humanities most frequent complaints. While dangerous diseases are being combatted on a daily basis, something as simple as bad posture is often overlooked. Bad posture can start off as a simple habit and soon lead to chronic back pain. Thus it is essential to maintain an ideal posture so as to reduce stress on the body. In this paper, monitoring of posture is done using flex sensor placed along the spine to detect the movement or bend. As posture changes from ‘ideal’ to ‘poor’, the user is alerted through a buzzer and LCD. A microcontroller is used to set the limits of ideal posture, which can be user specific. A load cell is used to monitor the variation in body weight and spine stress for poor and ideal postures under sitting and standing cases. The proposed system aims to implement a simple posture monitoring and correction system that can be set up at the work place with ease. This can serve to prevent cases of scoliosis and other spine issues which often start with poor posture.